Community Social Work in the context of housing: redefinition and challenges based on a case study - Morán Neches, Lorena; Rodríguez Suárez, Julio (Cuadernos de Trabajo Social, 2021)
As a central structure of society and a basic right of citizens, housing represents a key element for a dignified life and social integration. The loss of housing therefore signifies a material deprivation and, at the same time, a process of rupture that undermines the stability and health of those who experience it first-hand, who tend to be driven into exclusion. In this context, social work is a suitable and necessary agent for intervention in terms of both the consequences and causes of housing loss. This article reports a case study focusing on an intervention based on individual and community social work methodologies, taking place as part of a mass eviction process in a small settlement in the north of Spain. The article uses this particular experience to reflect on the deficient role that social work is playing in housing matters, following the care-based trend of one-off actions that lack continuity and fail to truly address the roots of the problem. The conclusion is that particularly in the context of eviction process, it is appropriate to set in motion other interventions from a comprehensive and community perspective. There is also a need for critical professional positioning that does not lose sight of the transformative objective of practice.
Keywords: Community Social Work; evictions; social intervention; support; inclusion